Energy Harvesting In Sub-6 GHz And Millimeter Wave Hybrid Networks - Muhammad, Nor Aishah; Anwar Apandi, Nur Ilyana; Seman, Norhudah; Yonghui, Li (Institute of Electrical and Electronics Engineers Inc., 2021)
Dense deployment of sub-6 GHz BSs not only enhance the network capacity but also improve the energy efficiency of wireless power transfer (WPT). Millimeter wave (MMW) technology features large antenna arrays with high directional beamforming gain and dense base station (BS) deployment that is also beneficial for WPT. This paper focuses on the hybrid deployment of sub-6 GHz and MMW networks, where the user equipment (UE) can simultaneously receive information and harvest energy from either sub-6 GHz or MMW BSs. By using a stochastic geometry framework, we develop analytical expressions for the energy coverage probability (ECP) and signal-to-interference-plus-noise coverage probability (SCP) of a typical user, where the BS and UE locations are modeled by either a Poisson point process (PPP) or a Poisson cluster process (PCP). We further incorporate the unique characteristics of MMW communications in the analysis and study the impact of the practical energy harvesting model on the system performance. Numerical results are provided to validate the accuracy of the analytical models. The results demonstrate that the ECP depends on the considered UE models, where for the PPP model, as the cluster size of BS increases, the ECP increases. In contrast, for the PCP model, the ECP decreases with the increasing of BS cluster size. The results also show that the energy coverage probabilities for both PPP and PCP users converge to the PPP model as the cluster size tends to infinity.